The Effect of Electronic Word of Mouth and Price on Purchase Decision Mie Ayam Bu Tumini at Yogyakarta - Lalu Supardin; Arisman; You She Melly Anne Dharasta (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This study aims to examine the effect of electronic word of mouth and price on purchase decision Mie Ayam Bu Tumini at Yogyakarta. The respondents in this study were consumers at Yogyakarta. The number of respondents in this study were 115 respondents. Sampling was done by purposive sampling technique. This study uses multiple linear regression analysis technique with SPSS as an analytical tool. The results of multiple linear regression test showed that: 1) Electronic word of mouth partially had a significant effect on purchase decision Mie Ayam Bu Tumini at Yogyakarta. 2) Price partially has a significant effect on purchase decision Mie Ayam Bu Tumini at Yogyakarta. 3) Electronic word of mouth and price simultaneously have a significant effect on purchase decision Mie Ayam Bu Tumini at Yogyakarta. Keywords: Electronic Word of Mouth, Price, Purchase Decision.